علاقة أسعار النفط والتضخم في الجزائر: The relationship between oil prices and inflation in Algeria - سي محمد كمال, (Journal of North African Economies, 2025)
This study examined the relationship between oil price changes and the inflation rate in Algeria from February 1994 to January 2022 using NARDL and the wavelets method. Based on wald test, our results fail to capture asymmetries in the relationship between oil price and inflation in the long run. On the contrary, we report a significant relationship between oil price shock increases and the inflation rate down in the short run. In contrast, there was a significant relationship between oil price reduction and the increased inflation rate. Finally, we find that wavelet coherence detects almost the relationship direction of oil prices to the inflation rate, indicating strong co-movement under the Covid19 period.